ANALISIS PERILAKU KEAGAMAAN REMAJA (STUDI KASUS DI KELURAHAN 2 ULU KOTA PALEMBANG) - Kurnia Oktaria; Fajri Ismail; Muhammad Win Afgani (CV. ADIBA AISHA AMIRA, 2023)
This paper aims to determine the religious behavior of adolescents in the 2 ulu sub-district of Palembang city. This paper uses the research method in this study is a qualitative method and this type of research includes the type of case study research where case study research is research conducted on a